Staff development needs for teacher educators in the Northern Province with regard to the implementation of the National Qualifications Framework - Kubheka, Kgadi Rose (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2000.